Application of the Smith Waterman and Jukes Cantor Algorithm in the Arrangement of the SARS CoV-2 Virus - Tony Yulianto; Mohamad Tafrikan; Rica Amalia; Emi Yunita; Moch. Haikal; Fathorrozi Ariyanto; Zuhrotul Hasanah (Journal of Natural Sciences and Mathematics Research, 2022)
In early 2020, the world was shocked by an outbreak of a new pneumonia that started in Wuhan, Hubei Province, which then spread rapidly to more than 190 countries and territories. This outbreak was named coronavirus disease 2019 (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). The spread of this disease has had a wide social and economic impact. There is still a lot of controversy surrounding this disease, including in the aspects of diagnosis, treatment, and prevention. Therefore, a study was carried out on studies related to COVID-19 that have been widely published since the beginning of 2020 until the end of March 2020.So to overcome this problem, the Smith Waterman Jukes Cantor Algorithm was made to align Covid19 by taking the a pair of DNA and RNA sequencesto align protein sequences. From this alignment, the percentage of identical and mutations will be known. The identical percentage in the genetic code will prove that although the symptoms caused by the disease are almost the same, the protein sequences are not necessarily the same. Based on the simulation results of the distance between sequences that produce a phylogenetic tree using the jukes cantor method, it was obtained that 4 groups of 26 sequences were divided into groups, namely, group 1 consists of 16 sequences, group 2 consists of 6 sequences, group 3 consists of 2 sequences, group 4 consists of 2 sequences. Based on these groups, it turns out that the China Wuhan sequence (sequence MT291826) is located in group 1 and other countries that are almost similar to the sequence in China Wuhan, namely the country of Timoe Leste with the sequence MT641766 also located in group 1.©2022 JNSMR UIN Walisongo. All rights reserved.